The level of well-being among small farmers: a case of Sindh province, Pakistan - Khushk, Ghulam Mujtaba; Abu Samah, Asnarulkhadi; Hamsan, Hanina; Ahmad, Nobaya (Publications International, 2016)
Worldwide activities at government and non-government level are being conducted to improve the quality of life and well -being of people. These activities need to be evaluated/ assessed to observe the impact on society. Thus, the present study attempted to asses such activity in the province of Sindh, Pakistan. This study was carried out using survey method. The targeted population of this study was the small farmers of three districts who participated in a crop maximization project(CMP-II). The sample size was 455 at significance level of 5%. The multistage sampling method was employed and responses were recorded on a six-point Likert scale questionnaire.This study assessed the level of well -being among small farmers of Sindh province. The level of well-being was divided into four sections namely; material conditions, quality of life, human solidarity and sustainability. The present study revealed that, there is an overall moderate level (M = 212.18; SD = 46.43) of well-being among the beneficiaries. It is, therefore, concluded that projects like crop maximization improves the quality of life of the people and eventually contribute to the well-being of the people.